الاحتياجات التدريبية لمعلمي المرحلة الثانوية في ضوء الكفايات اللازمة لرعاية الطلبة المتفوقين - الأغا، هانى عبدالقادر عثمان (جامعة النجاح الوطنية, 2019)
هدفت الدراسة إلى تحديد الاحتياجات التدريبية اللازمة لمعلمي المرحلة الثانوية أثناء الخدمات في ضوء كفايات المعلم لرعاية الطلبة المتفوقين. اتبعت الدراسة المنهج الوصفي (الأسلوب التحليلي). وتكونت أدوات الدراسة من أداتين: تمثلت الأولى في قائمة كفايات المعلم لرعاية الطلبة المتفوقين مكونة من (56 كفاية) موزعة على أربعة مجالات: كفايات معرفة المفاهيم الأساسية لرعاية وتربية الطلبة المتفوقين، كفايات تعرف الطلبة المتفوقين وطرق الكشف المستخدمة، كفايات إعداد البرامج وأساليب الرعاية للطلبة المتفوقين، الكفايات الشخصية لمعلم الطلبة المتفوقين، تم تطبيقها على (24) فردا من أساتذة الجامعات والمشرفين والمختصين في رعاية الفئات الخاصة؛ لتحديد الكفايات اللازمة لمعلمي المرحلة الثانوية لرعاية الطلبة المتفوقين، حيث تم استبعاد (6 كفايات) حصلت على ما نسبته أقل من (85%)، فيما تمثلت الأداة الثانية في استبانة الاحتياجات التدريبية للمعلمين لرعاية المتفوقين مكونة من (44) فقرة تم بناؤها في ضوء قائمة الكفايات التي تم إعدادها، حيث تم تطبيقها على (360 معلم ومعلمة). وقد توصلت الدراسة إلى أن مستوى الاحتياجات التدريبية لمعلمي المرحلة الثانوية تراوح بين (0.82- 0.89) لمجالات استبانة الاحتياجات و(0.86) للاستبانة ككل، كما توصلت الدراسة إلى وجود فروق دالة في تقدير المعلمين لاحتياجاتهم التدريبية تبعا لمتغير المؤهل العلمي لصالح الدراسات العليا، فيما أظهرت النتائج عدم وجود فروق دالة تبعا لمتغيري النوع وسنوات الخدمة. وفي ضوء النتائج أوصت الدراسة باتخاذ التدابير اللازمة لتنمية كفايات المعلمين لرعاية الطلبة المتفوقين من خلال إخضاعهم لبرامج تدريبية متخصصة في مجال عملهم؛ لتنمية الكفايات المهنية والاجتماعية اللازمة لهم، وذلك في مجالات التعامل مع الطلبة ذوي الاحتياجات الخاصة، وفي ضوء المحاور الرئيسة التي عكستها أبعاد استبانة الاحتياجات التدريبية التي أعدت في هذه الدراسة.
This Study aimed to identify the necessary training needs for Secondary Stage Teachers In-service Scope in the light of teacher's Competence for taking care the Gifted Students. The Study used the descriptive methodology (Style Implemented: The Analysis Style). The Study's tools were consisted into two tools: the first is a list of teacher's competence for taking care the Gifted Students which included from (65 Competencies) distributed in four Scope: The Competencies of essential Concepts Knowledge for taking Care the Gifted Students, Competencies of recognizing the Gifted Students and the used finding out method, Competencies of preparing programs and the styles of taking care for the Gifted Students, Personals competencies of Gifted Students teacher's, And was implemented at (24) Universities academic stuff, Supervisors and the specialists in the scope of taking care; to identify the necessary competencies needs for secondary stage teachers for taking care the Gifted Students, where (6 Competencies) were canceled which wasn't reach to the level (85%). On the other hand, the second tool acted on a questionnaire of necessary training for teachers for taking care the Gifted Students, which included from (44 Paragraph) which built in light of a list of competence, and it was implemented at (360 teachers). The study reached that the level of training needs for secondary school teachers was (0.82 - 0.89) for the dimensions of needs questionnaire and (0.86) for the questionnaire as a whole. The study also reached that there is a significant difference in the teachers' assessment of their training needs according to scientific qualification for postgraduate. And also that there are no significant differences according to sex and years of service. In the light of the results, the study recommended the development of teacher competencies to take care of higher Achiever students through subjecting them to specialized training programs in their field of work to develop the professional and social skills required for them in dealing with students with special needs. And on light of the main scope of the training needs questionnaire prepared in this study.
Keywords: الكفايات المهنية -- الاحتياجات التدريبية -- معلمو المرحلة الثانوية -- الطلاب المتفوقين -- رعاية الموهوبين